EFFECT OF LUNASIN-ENRICHED SOY EXTRACT ON HISTONE DEACETYLASE EXPRESSION IN DISTAL COLON EPITHELIAL CELLS FROM AOM/DSS-INDUCED MICE - KUSMARD, KUSMARDI; TARIGAN, TIFFANY ROSA SUDARSO; ESTUNINGTYAS, ARI; TEDJO, ARYO (International Journal of Applied Pharmaceutics, 2019)
Objective: Lunasin peptide, with its chemopreventive and chemotherapeutic abilities, is known to affect carcinogenesis via epigenetic regulation involving histone acetylation. This study investigated lunasin, which can be found in soy, and its effects towards histone deacetylase (HDAC] expression in a mouse model of carcinogenesis. Methods: Thirty Swiss Webster mice were grouped into normal, positive control, negative control, and experimental groups. Except for the normal group, mice underwent carcinogenesis induction through azoxymethane (AOM] and dextran sodium sulfate (DSS] injection. Experimental mice received lunasin-enriched soy extract at a dosage of 250 mg/kg BW (kilogram body weight), 300 mg/kg BW, and 350 mg/kg BW for 4 w. Distal colon samples were stained by using immunohistochemistry (IHC]. HDAC expression was measured by IHC optical density score. Results: Average HDAC expression was 202.4% in the normal group, 239.3% in the negative control, 175.25% in the positive control, 202.03% at 250 mg/kg BW dose, 219.53% at 300 mg/kg, and 166.68% at 350 mg/kg BW. There was no significant difference between HDAC expression at 250 mg/kg BW and 300 mg/kg BW soy extract. However, at 350 mg/kg BW soy extract there were significant changes in HDAC expression. Conclusion: lunasin in soy extract at a 350 mg/kg BW dose can decrease HDAC expression in a colorectal cancer carcinogenesis model.